CD100/Sema4D Increases Macrophage Infection by Leishmania (Leishmania) amazonensis in a CD72 Dependent Manner - Galuppo, Mariana K.; de Rezende, Eloiza; Forti, Fabio L.; Cortez, Mauro; Cruz, Mario C.; Teixeira, Andre A.; Giordano, Ricardo J.; Stolf, Beatriz S. (Frontiers in Microbiology, 2018)
Leishmaniasis is caused by trypanosomatid protozoa of the genus Leishmania, which infect preferentially macrophages. The disease affects 12 million people worldwide, who may present cutaneous, mucocutaneous or visceral forms. Several factors influence the form and severity of the disease, and the main ones are the Leishmania species and the host immune response. CD100 is a membrane bound protein that can also be shed. It was first identified in T lymphocytes and later shown to be induced in macrophages by inflammatory stimuli. The soluble CD100 (sCD100) reduces migration and expression of inflammatory cytokines in human monocytes and dendritic cells, as well as the intake of oxidized low-density lipoprotein (oxLDL) by human macrophages. Considering the importance of macrophages in Leishmania infection and the potential role of sCD100 in the modulation of macrophage phagocytosis and activation, we analyzed the expression and distribution of CD100 in murine macrophages and the effects of sCD100 on macrophage infection by Leishmania (Leishmania) amazonensis. Here we show that CD100 expression in murine macrophages increases after infection with Leishmania. sCD100 augments infection and phagocytosis of Leishmania (L.) amazonensis promastigotes by macrophages, an effect dependent on macrophage CD72 receptor. Besides, sCD100 enhances phagocytosis of zymosan particles and infection by Trypanosoma cruzi.